Chemical composition and antioxidant evaluation of volatile oils from thai medicinal plants - Kawaree R. (2014)
The volatile oils from fresh leaves of Emilia sonchifolia, Eupatorium odoratum and Spilanthes acmella were isolated by hydrodistillation. These volatile oils were determined for their antioxidant capacities as well as total phenolic compounds. The three well known methods: 1) 2,2′-azinobis(3 - ethylbenzothia - zoline - 6 - sulfonic acid) diammonium salt; ABTS+ assay, 2) ferric reducing antioxidant power (FRAP) assay, 3) lipid peroxidation assay were used, respectively, in order to obtain the antioxidant activity. The total phenolic content was evaluated according to the Folin - Ciocalteu procedure. Antioxidant screening of samples showed that the antioxidant activities of the selected volatile oils ranged from 40 to 276 μmol Trolox equivalent per gram, together with FRAP assay ranged from 60 to 350 u.mol Fe(II) equivalent per gram, and finally with the lipid peroxidation assays ranged from 9.1% to 61.55%. In total phenolic compounds screening assay, the results ranged from 12 to 308 GAE (μg/g). The results of this investigation significantly showed that the volatile oil of S. acmella possessed both of the highest antioxidant activity in all three assays as well as the total phenolic compounds. In addition, the volatile oil of S. acmella was analyzed through a combination of gas chromatography and mass spectrometry (GC-MS) coupled with mass selective detecter (MSD). The major components of S. acmella were germacrene-D (54.38%), trans-beta-caryophyllene (14.58%), beta-elemene (4.53%), nor-copaanone (2.44%) and bicyclogermacrene (2.15%), respectively. These results indicated that S. acmella has proved to be a good source of antioxidants that might serve to protect health and fight against diseases in the future.